2015
DOI: 10.1186/s40885-016-0041-1
|View full text |Cite
|
Sign up to set email alerts
|

The utility of biomarker risk prediction score in patients with chronic heart failure

Abstract: BackgroundChronic heart failure (CHF) has been remained a leading cause of cardiovascular morbidity and mortaluty. The risk stratification of CHF individuals based on clinical criteria and biomarkers' models may improve medical care and probably increase efficacy of treatment strategy. However, various predictive models approved for CHF patients appear to be distinguished in their prognostications. The study aim was to evaluate whether biomarker risk prediction score is powerful tool for risk assessment of thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
58
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(59 citation statements)
references
References 37 publications
0
58
0
1
Order By: Relevance
“…Moreover, there are data clarifying that even asymptomatic hyperuricemia associated strongly with long-term survival of CVD patients and individuals with chronic kidney disease throughout predialysis period and whose who undergoing hemodialysis procedures. In the Rotterdam Study high quartiles of normal rages of SUA and mild increased SUA level were more closely related to early-phase mechanisms of insulin resistance and diabetes mellitus rather than CV complications due to target organ damage progression [8]. Thus, predictive value of SUA in different patients at risk of HF is controversial and requires to be elucidated.…”
Section: Short Communicationmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, there are data clarifying that even asymptomatic hyperuricemia associated strongly with long-term survival of CVD patients and individuals with chronic kidney disease throughout predialysis period and whose who undergoing hemodialysis procedures. In the Rotterdam Study high quartiles of normal rages of SUA and mild increased SUA level were more closely related to early-phase mechanisms of insulin resistance and diabetes mellitus rather than CV complications due to target organ damage progression [8]. Thus, predictive value of SUA in different patients at risk of HF is controversial and requires to be elucidated.…”
Section: Short Communicationmentioning
confidence: 99%
“…Whether SUA could be an independent predictor of HF development is not fully clear. Recent clinical studies and some meta-analysis have shown that elevated SUA levels were associated with an increased risk of incident HF, observed in majority of patients with established chronic HF and relate to adverse clinical outcomes in HF [8][9][10][11]. However, the impact of uric acid on all-cause mortality and HF-related death was…”
Section: Short Communicationmentioning
confidence: 99%
“…Interestingly, there was an association between number of non-classical phenotype EPCs and diabetes mellitus, highly sensitive C-reactive protein, and Agatston score index , whereas CD45-CD34+ EPCs' number did not exhibit similar relations [26]. Moreover, incorporation of number of CD14+CD309+Tie2+ EPCs as a predictive biomarker into biomarker risk score for cumulative CV events in heart failure patients may sufficiently improve sensitivity, specificity, reliability and final discriminative value of the scale [27]. Yang et al [28] reported that count of circulating EPCs with immune phenotype CD34-/CD133+/KDR+ (VEGFR+) may exhibit osteogenic potential and strong correlates with coronary atherosclerosis at the early stage.…”
mentioning
confidence: 99%
“…In contrast, Bondar et al, (2014) [28] have guessed that the gene expression profiling might be useful rather for risk prediction in HF than for choosing HF treatment regime. Thus, the clinical implementation of the HF therapy based on genes scoring remains uncertain and requires more evaluation in the future [29].…”
Section: Introductionmentioning
confidence: 99%